STUDYING THE PROCESS OF TOOLING CYLINDRICAL GEARS - Sherov, Karibek (Journal of Applied Engineering Science, 2020)
The studies of the state of gears production show that there is a problem of ensuring the accuracy and quality of teeth tooling in finishing operations. To solve this problem, there has been developed a method of finishing the teeth of gears and a design of a special reeling tool for its implementation. A feature of the proposed method is its implementation on universal lathes. This article presents the results of an experimental study of the proposed method of tooling and studying the chip formation process. The research methodology is based on the scientific principles of engineering technology, the theory of chip formation, the theory of metal cutting and gear tooling. The metallographic method of research has also been used and the experiment has been planned. The results of experimental studies confirm the possibility of applying the proposed method for finishing side surfaces of the cylindrical gear teeth, at this there has been achieved roughness Ra = 1.25 ÷ 0.32 μm. The results of studying chip formation show that the tooling of the “shaver- squeegee” ensures high-quality crushing of chips, it somewhat weakens the structure of the chips and improves the working conditions of the tool and improves the quality of the finishing tooling of gear teeth.